1995
DOI: 10.1111/j.1476-5381.1995.tb15075.x
|View full text |Cite
|
Sign up to set email alerts
|

UTP‐ and ATP‐triggered transmitter release from rat sympathetic neurones via separate receptors

Abstract: In rat cultured sympathetic neurones, UDP, UTP and ATP at micromolar concentrations triggered Ca2"-dependent and tetrodotoxin-sensitive [3H]-noradrenaline release. The overflow evoked by UTP or ATP was similar at 100 ,umol I', the concentration used in all subsequent experiments. Pre-exposure of the neurones to 100 pumol I' UTP significantly reduced ensuing secretory effects of UTP but not of ATP. Conversely, pre-exposure to ATP diminished the overflow due to ATP but not that due to UTP. In the presence of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 9 publications
(9 reference statements)
1
32
0
Order By: Relevance
“…ATP, nicotine, or 25 mM K' triggered transmitter release in a partially TTX-resistant manner, and the release remaining in the presence of TTX was not enhanced by linopirdine. These TTX-resistant components of stimulation-evoked release involve direct stimulatory actions at presynaptic sites (Boehm and Huck, 1995;Boehm, 1999). Hence, linopirdine appears unable to enhance noradrenaline release via a presynaptic site of action, which supports the idea that K, channels are located at the somatodendritic region rather than at presynaptic axon terminals of SCG neurons.…”
Section: Enhancement Of Stimulation-evoked Transmitter Release By Linsupporting
confidence: 51%
See 1 more Smart Citation
“…ATP, nicotine, or 25 mM K' triggered transmitter release in a partially TTX-resistant manner, and the release remaining in the presence of TTX was not enhanced by linopirdine. These TTX-resistant components of stimulation-evoked release involve direct stimulatory actions at presynaptic sites (Boehm and Huck, 1995;Boehm, 1999). Hence, linopirdine appears unable to enhance noradrenaline release via a presynaptic site of action, which supports the idea that K, channels are located at the somatodendritic region rather than at presynaptic axon terminals of SCG neurons.…”
Section: Enhancement Of Stimulation-evoked Transmitter Release By Linsupporting
confidence: 51%
“…Previously, activation of either nicotinic acetylcholine receptors (Boehm and Huck, 1995) or ATP P2X receptors (Boehm, 1999) has been found to trigger noradrenaline release from SCG neurons in a partially TTXsensitive manner. Therefore, the above experiments were repeated with nicotine (100 p M ) or ATP (300 pM) as secretory stimuli.…”
Section: Enhancement Of Stimulation-evoked Overflow By Linopirdine Ismentioning
confidence: 99%
“…Thus, UTP inhibits the M-current and excites some sympathetic neurones (e.g., Siggins et al, 1977;Adams et al, 1982;Cuevas et al, 1997); while Von Kugelgen et al (1994) have described inhibitory eects of UTP on evoked transmitter release from brain tissue (though the receptors responsible for these eects have not been fully characterized). On the other hand, UTP and UDP (but not ATP) have been reported to trigger transmitter release from sympathetic terminals through a P2Y receptor (Boehm et al, 1995;Von Kugelgen et al, 1997): this could be related to the increase in intracellular Ca 2+ following phospholipase C stimulation. The balance between inhibitory and facilitatory eects on transmitter release might then be dierent in peripheral and central nerve terminals because of the complement of receptors/eectors involved.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium flux through the P2X receptors is sufficient to evoke the release of norepinephrine. Boehm et al (30,31) showed that norepinephrine was released by ATP from cultures for rat superior cervical ganglion cells, even when voltage-gated calcium channels were blocked by cadmium (see also Ref. 487).…”
Section: Sympathetic Neuronsmentioning
confidence: 99%